In-Vitro Synergestic Effects Between Bifidobacterium Pseudocatenulatum G4 and Inulin on Human Gastrointestinal Tract Microbial Composition - Othaman, Muhammad Anas (2009)
The eagerness in finding the most effective probiotic strain has attracted many investigations. Bifidobacterium pseudocatenulatum G4, strain isolated from free-living infant was reported to have characteristics as probiotic candidate. Meanwhile, inulin is a known natural source of carbon that can act as a prebiotic substance. The consumption of probiotic, prebiotic, and its combination (synbiotic) was reported to have the ability to alter microbial composition in human gastrointestinal tract (GIT). In this study, the effects of B. pseudocatenulatum G4 (probiotic), inulin (prebiotic) and its combination (synbiotic) towards the human GIT microbial composition were evaluated in vitro. The effects of inulin incorporated in chocolate products as one of its ingredients were also tested. Real-time PCR assay with selected genus- and species-specific primers were used as a tool in identification and enumeration of selected bacterial strain in fermentation of mixture of bacteria from human faecal sample while dilution and plate count technique was used to enumerate the bacterial cell in fermentation of pure culture bacteria. The morphology of the tested Bifidobacterium strains was observed and the species was confirmed by molecular method targeting 16S rRNA gene. In pure culture batch fermentation of tryptone peptone yeast (TPY) medium supplemented with 0.5% inulin, B. pseudocatenulatum G4 grew at the growth rate of 0.53 ± 0.06 log10 h-1 as compared to other Bifidobacterium strains namely B. breve ATCC 15700, B. longum BB536, and B. infantis ATCC 15697 which grew at 0.45 ± 0.04 log10 h-1, 0.31 ± 0.08 log10 h-1, and 0.72 ± 0.03 log10 h-1, respectively. The same amount of inulin was then introduced into darkand milk chocolate and caused B. pseudocatenulatum G4, B. breve ATCC 15700, B. longum BB536, and B. infantis ATCC 15697 to grow at 0.54 ± 0.06, 0.44 ± 0.04, 0.36 ± 0.05, 0.73 ± 0.02 log10 h-1 for dark chocolate and 0.57 ± 0.05, 0.46 ± 0.03, 0.41 ± 0.04, 0.75 ± 0.01 log10 h-1 for milk chocolate respectively. Some of the chocolate ingredients had also influenced the growth of B. pseudocatenulatum G4. The addition of 0.5% of cocoa liquor in TPY medium caused B. pseudocatenulatum G4 to grow at 0.29 ± 0.03 log10 h-1, and isomalt at 0.59 ± 0.05 log10 h-1 compared to TPY medium without any additional carbon source which grew at 0.19 ± 0.02 log10 h-1, while the addition of cocoa butter did not support the growth of B. pseudocatenulatum G4. In 24 hours batch fermentation of human faecal bacteria, B. pseudocatenulatum G4 (Probiotic) showed its probiotic effects by inhibiting the growth of Salmonella and Enterococcus faecalis. The addition of inulin (Prebiotic) selectively supported the growth of Bifidobacterium and Lactobacillus as well as inhibits the growth of Bacteroides, Salmonella, and E. faecalis. The synbiotic combination of B. pseudocatenulatum G4 and inulin (Synbiotic) showed a synergestic effect as they reduced the number of Bacteroides, Salmonella, and E. faecalis better than Probiotic or Prebiotic alone. Synbiotic chocolate preparations (DCsynbiotic and MCsynbiotic) showed better synergestic effect with B. pseudocatenulatum G4 compared to Synbiotic when Bifidobacterium increased at 1.64 log10 (DCsynbiotic) and 1.67 log10 cells/ml (MCsynbiotic) from the initial counts. Lactobacillus also increased its cell number higher than Synbiotic treatment. Nevertheless, synbiotic chocolate preparations also gave a positive result towards the growth of potential pathogenic bacteria when compared to Synbiotic. However, the inhibition pattern still can be observed on Salmonella and E. faecalis when compared to glucose (control). The antimicrobial action was largely due to the pattern of lactic and acetic acid production in fermentation. Here, the synbiotic approach was more efficient than prebiotic or probiotic alone to modulate the human GIT microbial composition and B. pseudocatenulatum G4 with inulin is a compatible synbiotic pair to perform the function.